Uniformity of utilization distribution of the teeth of the cutter - Sovilj, Bogdan; Mitrović, Ratko (Journal of Production Engineering, 1984)
In the work, the uniformity of wear of the teeth of the taper cutter and the optimal size of the axial movement of the taper cutter and the production conditions were determined. By applying the optimal displacement, the stability of the tool is increased, which leads to a reduction in tool costs and wear costs.